Enhancing High School Students' Mathematical Problem-Solving Skills through Interactive Media: A Classroom Action Research Approach - Choirudin, Choirudin; Masuwd, Mowafg Abrahem; Lubis, Maesaroh (Universitas Muhammadiyah Malang, 2025)
To realize Indonesia Emas, where digitalization is prevalent across various fields today, it is essential to cultivate computational thinking skills through mathematics learning. This study evaluates the effectiveness of interactive media in enhancing mathematical problem-solving skills among senior high school students. Utilizing a Classroom Action Research (CAR) approach, 60 grade XII students from a high school in Jakarta participated in this research over one semester. Interactive media, including computer applications and educational games like